PENINGKATAN KINERJA PEGAWAI MELALUI PENDIDIKAN DAN PELATIHAN STUDI KASUS BADAN PUSAT STATISTIK KABUPATEN MAGELANG - Kurnia, Marlina (Universitas Muhammadiyah Magelang, 2007)
Badan Pusat Statistik (BPS) in duty management and its function strategic, require to be supported by personnel (human resource) owning high performance. Make-up of human resource represent the requirement of necessary for organization in reaching targets. Institution or company comprehending about its important oen the human resource which with quality and rely on, will ready toinvest its fund into programs of education and training utilize the make-up of ability and its human resource quality. This research aim to know the influence of education and training to officer performance at Badan Pusat Statistik (BPS) of Regency Magelang. This research population is officer of Badan Statistik (BPS) of Regency Magelang. Pursuant to method of intake sample by using census method (sum up the responder of equal to amount sample) obtained by sample as much 36 responder. Education and training to Stastical Center Body officer performance Regency Magelang. Education represent the variable having an dominant effect to Badan Pusat Statistik (BPS) officer performance of Magelang Regency.